Bacterial cellulose production from extracted date syrup - Lotfiman, Samaneh (2010)
Bacterial cellulose (BC) is used in various industries such as food, paper, electronic and biomedical. However, the current productivity is still very low. Therefore, it is imperative to seek for BC production by utilizing other sources. Therefore, the main objectives of this work were (i) to quantify and characterized sugars from date using various extraction methods, (ii) to optimize bacterial cellulose production using the extracted sugars as substrate, (iii) to characterize and quantify bacterial cellulose production from the various extraction methods used. It is predicted that replacing glucose in Hestrin and Schramm medium with extracted date syrup will alter the specific properties of the BC produced. To achieve these objectives, different sugar extraction methods were compared, namely stirred and ultrasonic-assisted water extraction, and solvent extraction using 50% ethanol and 80% methanol as solvents. The results of the work showed that sugar extraction from date by water with ultrasonic assisted, extracted the highest amount of total sugar (79%). The amount of extracted total sugar via water (stirring), ethanol and methanol were 71%, 67% and 57% respectively. Furthermore, the results revealed that BC was formed in the medium where date syrup was used as a carbon source. The enriched medium utilizing extracted syrup produced from 30 g dry date/l via ultrasonic assisted water extraction method was able to produce 186% BC more than that produced in Hestrin and Schramm medium. SEM analysis of the BCs showed fine nanofibers (60-90 nm) and smooth surface. The presence of C=O amid bond and one of collagen features, in the BC exhibited by FTIR demonstrated that the BC produced in the enriched medium has the potential to be used in medical application, i.e. wound dressing. The BC mechanical tests results revealed considerable improvement in the Young Modulus, tensile stress and elongation at break values over the BC formed in the Hestrin and Schramm medium, namely; 29-80%, 50-140% and 33-119% respectively. To conclude, this work has successfully achieved the outlined objectives. The properties of the BC characterized illustrated that BC can be re-engineered by using date fruit as a carbon source; this has created a more promising future for BC especially in medical applications.